Efeitos da urbanização no uso e cobertura do solo e na temperatura de superfície da bacia hidrográfica do Ribeirão Cambé - Paraná - Lopes, Maria Clara dos Santos (2024)
Implementing monitoring practices in these areas, based on different approaches to sustainable development, is necessary to mitigate the impacts of urbanization in a watershed. This study aimed to analyze the impacts of urbanization on the Ribeirão Cambé Watershed (RCW), using geoprocessing techniques to map changes in land use and land cover and assess their influence on land surface temperature (LST) and potential environmental impacts. For this purpose, a systematic literature review was conducted to map studies associated with the influence of urbanization in the area, focusing on three analysis approaches: bibliometric analysis, InOrdinathio analysis, and content analysis. Environmental analyses were performed in the watershed, including morphometric characterization, monitoring of land use and land cover patterns in four analyzed classes (urban area, rural area, forest formation, and aquatic environment), using data provided by MapBiomas, application of a Rapid Assessment Protocol for Urban Rivers (PARU), and identification of LST using data obtained from Landsat satellite series and emissivity extracted from NDVI and coverage factor, to enable statistical analysis to understand if there is a temperature difference in different types of land use and land cover. Through the systematic literature review, it was possible to identify studies focused on urbanization issues, recognize their metrics, identify the most relevant articles, and understand the themes that were most studied. Morphometric characterization revealed that the watershed predominantly has undulating relief, with a low tendency for floods and regular drainage. The multitemporal analysis of land use and land cover patterns over a 36-year interval showed that the watershed transitioned from predominantly rural (63%) in 1985 to urban, totaling 49% in 2021. Based on the results of the PARU application, the RCW could be classified as having an overall good condition (59.1), although there are areas with solid waste presence. Through LST analysis, extreme temperature points in the RCW were identified, with maximum values (37°C in 1985, 38°C in 2005, 36°C in 2015, and 45°C in 2021) associated with rural areas, while minimum values (19°C in 1985, 20°C in 2005, 15°C in 2015, and 27°C in 2021) were found in forested areas. The Kruskal Wallis test identified a significant difference between surface temperature values and normalized vegetation index, and the Dwass Steel Critchlow Fligner multiple correlation test identified that temperatures are statistically different for the studied land use classes (rural area, urban area, forest formation, and aquatic environment). Thus, the importance of green areas in rural environments is understood to mitigate high surface temperatures and provide thermal comfort.